Analisis Hubungan Integritas, Kreativitas, Serta Kualitas Layanan Konsultan Pajak Terhadap Kepatuhan Wajib Pajak Individu Pengguna Jasa Bersertifikat A di Bandung. (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of integrity, creativity, and service quality of tax consultants on individual taxpayers’ compliance in Bandung City. The research background highlights the important role of tax consultants as strategic partners of the Directorate General of Taxes in supporting the achievement of voluntary compliance, which is one of the key elements in optimizing state revenue. Tax consultants not only act as intermediaries but also as professional advisors who are expected to provide services based on ethical standards, innovative solutions, and a high degree of service quality to taxpayers. The research employed a quantitative approach with a survey design, using structured questionnaires distributed to individual taxpayers who utilized the services of certified Level A tax consultants in Bandung City. Data collected were analyzed through multiple linear regression to test the simultaneous and partial effects of the independent variables on taxpayer compliance. Statistical tools included the partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²).The findings indicate that integrity, creativity, and service quality each have a positive and significant impact on taxpayer compliance. Furthermore, the adjusted coefficient of determination (R²) of 69.2% demonstrates that the three independent variables collectively explain most of the variation in taxpayer compliance, while the remaining 30.8% is attributed to other external factors not examined in this study. These results underscore the necessity of strengthening professionalism and innovation in tax consulting practices. Inconclusion, enhancing taxpayer compliance requires a synergistic integration of consultant integrity, creative problem-solving approaches, and superior service quality. The study suggests that sustainable compliance strategies in the taxation sector must be developed through collaborative efforts between tax authorities, tax consultants, and taxpayers. This ensures not only increased compliance rates but also the establishment of a fair, transparent, and accountable taxation system that contributes significantly to state financial stability.